The strings on David's Harp: religious ritual as a container for spirituality. Issue 1 (2nd January 2019) - Sasso Eisenberg, Sandy
ABSTRACT: Religion and spirituality have often been defined over against each other. The spontaneous, emotional and experiential nature of the spirit has been seen as preferential to the structured, fixed, and predictable nature of religious ritual. Religion education for children has moved away from the performance of ritual behaviour toward creating an environment to nurture the innate spiritual nature of children. This paper questions whether the pendulum has swung too far, neglecting rituals that have sustained religious and communal life for generations, and considers ways of reimagining traditional ritual as a way to encounter the spirit and build community.